A New Species of the Genus Adelophryne (Anura: Eleutherodactylidae: Phyzelaphryninae) from the Atlantic Forest of Northeastern Brazil - Lourenço-De-Moraes, Ricardo; Lisboa, Barnagleison Silva; Oliveira Drummond, Leandro De; De Melo Moura, Carina Carneiro; Barbosa De Moura, Geraldo Jorge; Lyra, Mariana Lúcio [UNESP]; Guarnieri, Miriam Camargo; Mott, Tamí; Hoogmoed, Marinus Steven; Santana, Diego José (Herpetologists League, 2021)
Species in the Adelophryne genus consist of diminutive, agile, and secretive frogs that inhabit forest leaf litter and have direct development. Species richness within Adelophryne was previously underestimated, and several new species have recently been described. Here, we describe a new species of Adelophryne from the Atlantic Forest in the Brazilian states of Alagoas, Pernambuco, and Paraíba. The new species is characterized by its small body size, small and distinct tympanum, toes with subarticular tubercles, fingers mucronate, three phalanges in the Finger IV, and an advertisement call composed of one single pulsed note with a high dominant frequency. The new species is phylogenetically related to other Adelophryne species of the Northern Atlantic Forest Clade and is endemic to the Pernambuco Endemism Centerin the Atlantic Forest biodiversity hotspot.
Keywords: Alagoas; Amphibia; Biodiversity; Hotspot; Miniature; Paraíba; Pernambuco